The quality of life in hemodialysis patients referring to hospitals of Zahedan University of Medical Sciences - Maryam Seraji; Davoud Shojaeezadeh; Roya Sadeghi (Tehran University of Medical Sciences, 2018)
Background: Patients with chronic and advanced kidney failure, who undergo hemodialysis treatment due to various drug therapies, encounter basic problems in their life style; consequently, these conditions affect both their physical and psychosocial state. The main purpose of this study was to determine the quality of life of hemodialysis patients referred to Zahedan University of Medical Sciences in Khatam-Al-Anbia and Ali-Ebnabitaleb hospitals in 2017. Methods: This is a descriptive-analytical study. All patient participants (n=129) referring to Zahedan hemodialysis clinics completed a questionnaire which included two sections: demographic data (7 questions) and Kidney Diseases Quality of Life (KDQOL) (24 questions) whose validity and reliability had been confirmed in previous studies. Data analysis was conducted through SPSS software v. 19 using statistical tests such as ANOVA and Independent T-test. Results: Of 129 hemodialysis patients, %58.9 were men. %41.2 of participants were 46-65 years old. The duration of kidney failure in %63.6 of patients was between 1 to 5 years. The participants' mean (SD) score of quality of life was 42.51±1.21. Moreover, results revealed that there was a statistically significant relationship between quality of life and age (P = 0.048) and kidney disease state (P=0.026). A positive and significant association was also observed between education (P=0.03), sex (P=0.04), Job (P=0.04), income level (P=0.043) and quality of life. Conclusion: The findings of the current study showed that illiteracy or elementary education, Joblessness, and low income may increase duration of dialysis and reduce the quality of life in dialysis patients. Thus, it is necessary to provide these patients with more social support and take their welfare condition into account.